Examining the correlates of current smoking among off-reserve First Nations, Métis and Inuit youth: Evidence from the 2012 Aboriginal Peoples Survey. (June 2017) - Van Bewer, Vanessa; Woodgate, Roberta L.
Highlights: Factors associated with smoking were examined among a sample of Aboriginal youth. Approximately 27% of Aboriginal youth were current smokers. Smoking was associated with speaking an Aboriginal language. Smoking was not associated with traditional activities. Heavy drinking is highly associated with smoking among Aboriginal youth.